Assessment of the effects of aquatic therapy on global symptomatology in patients with fibromyalgia syndrome: a randomized controlled trial - Munguía-Izquierdo, Diego; Legaz-Arrese, Alejandro (Archives of physical medicine and rehabilitation, 2008)
To evaluate the effects of a 16-week exercise therapy in a chest-high pool of warm water through applicable tests in the clinical practice on the global symptomatology of women with fibromyalgia (FM) and to determine exercise adherence levels. A randomized controlled trial. Testing and training were completed at the university. Middle-aged women with FM (n=60) and healthy women (n=25). A 16-week aquatic training program, including strength training, aerobic training, and relaxation exercises. Tender point count (syringe calibrated), health status (Fibromyalgia Impact Questionnaire); sleep quality (Pittsburgh Sleep Quality Index); physical (endurance strength to low loads tests), psychologic (State Anxiety Inventory), and cognitive function (Paced Auditory Serial Addition Task); and adherence 12 months after the completion of the study. For all the measurements, the patients showed significant deficiencies compared with the healthy subjects. Efficacy analysis (n=29) and intent-to-treat analysis (n=34) of the exercise therapy was effective in decreasing the tender point count and improving sleep quality, cognitive function, and physical function. Anxiety remained unchanged during the follow-up. The exercise group had a significant improvement of health status, not associated exclusively with the exercise intervention. There were no changes in the control group. Twenty-three patients in the exercise group were exercising regularly 12 months after completing the program. An exercise therapy 3 times a week for 16 weeks in a warm pool could improve most of the symptoms of FM and cause a high adherence to exercise in unfit women with heightened FM symptomatology. The therapeutic intervention's effects can be assessed through applicable tests in the clinical practice.